High-rate breakthrough cancer pain and tumour characteristics - literature review and case series - Arturo Cuomo; Anastasios Boutis; Francesca Colonese; Davide Nocerino (BioExcel Publishing Ltd, 2023)
Cancer pain requires careful comprehensive patient evaluation and an appropriate and personalized clinical approach by a trained multidisciplinary team. The proper assessment of breakthrough cancer pain (BTcP) is part of an all-inclusive multidimensional evaluation of the patient. The aim of this narrative review is to explore the relationship between high-rate BTcP, which strongly impacts healthrelated quality of life and tumour characteristics, in the face of novel approaches that should provide guidance for future clinical practice. The presentation of short, emblematic clinical reports also promotes knowledge of BTcP, which, despite the availability of numerous therapeutic approaches, remains underdiagnosed and undertreated. This article is part of the Management of breakthrough cancer pain Special Issue: https://www.drugsincontext.com/special_issues/management-of-breakthrough-cancer-pain